Feasibility of an Advance Care Planning Program (ACP) for Korean Community-Dwelling Older Adults and ACP Training of Advance Practice Nurses. Issue 3 (3rd July 2021) - Park, Mihyun; Park, Eun-Jun; Jo, Minjeong; Ahn, Jinhee
ABSTRACT: This study aimed to develop a locally suitable advance care planning (ACP) program for older community-dwelling adults and a training program for nurse facilitators in Korea, and to evaluate their feasibility from the facilitators' experiences. This was a mixed methods pilot study that assessed the feasibility of an ACP program by analyzing survey, checklist, and focus group interview data. The ACP program was named CLOSE (Communicating and Listening to Our Seniors' voices about End-of-life care). Home health care nurses (N = 9) participated in this study. The participants reported that CLOSE was applicable to older community-dwelling adults and the training program was useful for increasing facilitator competency. We suggest some lessons from this pilot study that can be used to improve the ACP program and encourage community health nurses to participate in ACP as facilitators.